Finite-element modelling of compressed fibrous materials: Modelling of the sound absorption and transmission properties of multi-layer assemblies including compressed fibrous materials and comparison to the results obtained from the transfermatrix- method and measurements - Panter, Pablo; Kåberger, Axel (My University, 2020)
This thesis work addresses the finite-element-method (FEM) modelling of the sound transmission and absorption properties of multi-layer systems including compressed fibrous materials. The investigated system is a noise shield which is used for encapsulating the engine in trucks. Today, the complex surface impedance is used to represent this system in FEM modelling. With this method, the back face of the noise shield is considered as fully reflective and there is no possibility to assess transmission through the encapsulation. The present thesis work aims for improving the currently employed methods by taking more complex information into account, specifically by applying Biot’s theory in the modelling of poroelastic materials. The results of different FEM models are compared to the results obtained fromtransfermatrix- method (TMM) models and measured data. Three out of seven models have been found to provide a good agreement between the FEM and TMM results as well as to measured data of the absorption coefficient. A mesh size sensitivity study indicates that six to seven linear elements per smallest wavelength are sufficient to decrease the mesh-related error in the calculated sound transmission loss to below1 dB for the investigated system. However, it has been found that today there are still hindering limits in terms of computational power when modelling soft poroelastic materials in FEM due to the small apparent wavelengths.
Keywords: FEM, poroelastic, multi-layer, sound transmission, sound absorption